2011
DOI: 10.1155/2011/541487
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study on Apoptosis Induced by Strontium‐89 in HumanBreast Carcinoma Cell Line

Abstract: Many radiopharmaceuticals used for medical diagnosis and therapy are beta emitters; however, the mechanism of the cell death caused by beta-irradiation is not well understood. The objective of this study was to investigate the apoptosis of human breast carcinoma MCF-7 cell lines induced by Strontium-89 (89Sr) and its regulation and control mechanism. High-metastatic Breast Carcinoma MCF-7 cells were cultured in vitro using 89Sr with different radioactive concentration. The inhibition rate of cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…radionuclides with longer half-lives) may be disadvantageous for patients with short life expectancy (Krishnan et al, 2014 A major challenge associated with the palliative treatment of bone pain using selective radiopharmaceuticals is to deliver the adequate dose of ionizing radiation to the bone lesion while minimizing the dose to healthy bone sites and adjacent tissues. Consequently, the emitted particles should have an energy and tissue penetration range compatible with the volume of the lesion to be irradiated (Chakraborty et al, 2008;Daha et al, 2010;Wang et al, 2011 (Zalutsky and Vaidyanathan, 2000). Therefore, owing to their short penetration range, systemic tumor-targeted radiotherapy with Auger electrons or alpha particles often yields lower toxicity to the bone marrow in comparison to β -particles (Tavares and Tavares, 2010).…”
Section: The Ideal Radiopharmaceutical For Bone Pain Palliationmentioning
confidence: 99%
See 1 more Smart Citation
“…radionuclides with longer half-lives) may be disadvantageous for patients with short life expectancy (Krishnan et al, 2014 A major challenge associated with the palliative treatment of bone pain using selective radiopharmaceuticals is to deliver the adequate dose of ionizing radiation to the bone lesion while minimizing the dose to healthy bone sites and adjacent tissues. Consequently, the emitted particles should have an energy and tissue penetration range compatible with the volume of the lesion to be irradiated (Chakraborty et al, 2008;Daha et al, 2010;Wang et al, 2011 (Zalutsky and Vaidyanathan, 2000). Therefore, owing to their short penetration range, systemic tumor-targeted radiotherapy with Auger electrons or alpha particles often yields lower toxicity to the bone marrow in comparison to β -particles (Tavares and Tavares, 2010).…”
Section: The Ideal Radiopharmaceutical For Bone Pain Palliationmentioning
confidence: 99%
“…For example, the decay of 125 I has been shown to lead to the deposition of a very high dose (≈10 9 cGy/decaying atom) in the immediate vicinity (≈2 nm 3 ) of the decay site and a sharp and significant drop in the energy deposited (from ≈10 9 to ≈10 6 cGy) as a function of increasing distance (few nanometres) from the decaying 125 I atom (Kassis, 2011). For example, when 125 I is localized within the cytoplasm, the survival curve is of the low LET type and the number of decays needed to reduce survival is ≈80 times that of DNA-incorporated 125 I (Kassis, 2011 (Abbasi, 2012(Abbasi, , 2011Argyrou et al, 2013a;Bączyk, 2011;Bryan et al, 2009;Chakraborty et al, 2008;Daha et al, 2010;Das et al, 2009;Harrison et al, 2013;Lewington, 2005;Máthé et al, 2010;Neves et al, 2005;Nilsson et al, 2013bNilsson et al, , 2007Nilsson et al, , 2005aNilsson et al, , 2005bPandit-Taskar et al, 2014;Ramdahl et al, 2013;Sartor, 2004;Simón et al, 2012;Sivaprasad and Rajagopal, 2012;Tomblyn, 2012;Vigna et al, 2011;Volkert and Hoffman, 1999;Wang et al, 2011). Despite the growing number of radionuclides investigated for treatment of bone metastases, the use of 89 Sr and 153 Sm still accounts for the bulk of radiopharmaceutical bonetargeted therapeutics in the clinical context and the majority of the review articles available in the literature focus on those two radionuclides.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2011) found the use of strontium-89 was successful in eliminating human breast carcinoma cells. In the context of a radioactive meltdown or attack, the targeting process used by medicinal science is no longer in place, and apoptosis occurs in healthy cells as well.…”
Section: Cell Apoptosismentioning
confidence: 99%
“…In order or maximize the therapeutic effect and minimize normal-tissue irradiation, the radiation emitted by the targeted radionuclide should have an energy and tissue penetration range compatible with the volume of the lesion to be irradiated (Chakraborty et al 2008;Wang et al 2011). Therefore, studying the effects of particulate radiation at the cellular level is of interest to determine the suitability of a given radionuclide for target-tumor radiotherapy.…”
Section: Introductionmentioning
confidence: 99%